KEEFEKTIFAN HUKUMAN TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS III SD N 1 MAGELUNG KENDAL - Rahmat Rais; Hesti Dwi Winarni (Universitas PGRI Semarang, 2013)
The research is motivated by the results of learning mathematics that has not reached the KKM and lack of student motivation to learn mathematics. This study point to determine the success achieved by the third-grade students in elementary school 1 Magelung Kendal on outcomes and students' motivation to learn mathematics using a learning punishment. This research is quantitative and designs used are Posttest - Only Control Design . The population in this study were all students of class III A and III B. Methods of data collection in this study is the documentation , test results of psychological learning and student motivation scale. The results showed the average value of the experimental group students' learning outcomes are higher than the 79.25 value - average control group of student learning outcomes is 61.93 . Calculation of classical completeness experimental group obtained t ?é?¼ count = 3.13 with significance level of 5% greater than the table = 1.67 penalty proves learning can improve student learning outcomes. Also obtained the average value of the psychological scale experimental group is 77.44, which means achieving the students' motivation in the high category . Results of analysis using t-test with a significance level of 5% obtained t = 3.13 is greater than table = 1.67 . Because t > t table then H0 is rejected . So the results of experimental class learning over classroom learning outcomes control . Between classroom learning model that uses sentence with the class that does not use punishment learning model is no difference learning outcomes of students with learning sentence with student learning outcomes with conventional learning . Based on these results , suggestions can be given is the need for learning with penalty ntuk improve outcomes and students' motivation in learning mathematics